EFEKTIVITAS PENERAPAN MEDIA PEMBELAJARAN BERBASIS ETNOMATEMATIKA TERHADAP MATA PELAJARAN MATEMATIKA PADA MATERI BANGUN RUANG DIKELAS V - Nurkamila, - (2022)
During this pandemic, the development of the world of education cannot be separated from the influence of technology and learning media. So there are several subjects that are required to use learning media in the learning process. One example of a subject that must use learning media is mathematics, where mathematics is a subject studied by students at the formal education level starting from elementary school. The problem that is often experienced by students in learning mathematics is the difficulty in understanding a mathematical concept. The main factor causing this problem is educators who still use learning methods that are not in accordance with the situation and cultural background of students. Ethnomathematics is a form of culture-based education. Based on this, the researchers used ethnomathematics-based learning media in learning mathematics on the material of spatial structure. Researchers conducted research with Quasi Experimental Design in the form of Nonequivalent Control Group Design. There are two groups of students who are the object of research; the control group with ordinary learning (conventional) and the experimental group with ethnomathematics-based learning. The results of the analysis obtained show that the two data are in a normally distributed and homogeneous data with the t-test on the posttest data showing that Hₒ is rejected, indicating that there is a difference in student results between the two groups. This is indicated by the results of the t-test which produces a significance value of 0.031 and 0.034 which means that the value is less than 0.05 so that Hₒ is rejected, meaning that there is a difference, and from the N-Gain test, the final result of the experimental group is of high value with the criteria showing that ethnomathematics-based learning is very effectively applied in elementary schools. Most of the students gave a positive response to ethnomathematics-based learning. The interest given by students to ethnomathematics-based learning with the existence of learning media that connects subject matter with culture.